Studies of surface nanostructure formation due to swift heavy ion irradiation under grazing incidence. (July 2015) - Gruber, E; Lattouf, E; Bergen, L; Salou, P; Grygief, C; Wang, Y Y; Ochedowski, O; Benyagoub, A; Levavasseur, D; Rangama, J; Lebius, H; Ban d'Etat, B; et al.
Synopsis: In this contribution we present new experimental results for swift heavy ion irradiation under grazing incidence. This particular collision geometry forces the track formation to a region close to the surface, sometimes visible as a chain of individual nanodots, whose length can be controlled by the angle of incidence. For irradiation of mica surfaces a new track form is observed.